2021
DOI: 10.1098/rstb.2020.0105
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosome evolution from a heteromorphic to a homomorphic system by inter-population hybridization in a frog

Abstract: Sex chromosomes generally evolve from a homomorphic to heteromorphic state. Once a heteromorphic system is established, the sex chromosome system may remain stable for an extended period. Here, we show the opposite case of sex chromosome evolution from a heteromorphic to a homomorphic system in the Japanese frog Glandirana rugosa. One geographic group, Neo-ZW, has ZZ-ZW type heteromorphic sex chromosomes. We found that its western edge populations, which are geographically close to anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…And vice versa, that two taxa exhibit the same chromosome pair as sex chromosomes does not necessarily mean their sex determination systems are homologous: the same pair of autosomes can be independently co-opted for the function of sex chromosomes (e.g. [71,75,128]; for overview in amniotes see [34]), or there might be turnovers of sex determination systems by the emergence of a new sex-determining locus within the same sex chromosome pair [66,129] (cases 15, 18 and 20 in figure 2).…”
Section: Is the Sex Chromosome Differentiationmentioning
confidence: 99%
See 2 more Smart Citations
“…And vice versa, that two taxa exhibit the same chromosome pair as sex chromosomes does not necessarily mean their sex determination systems are homologous: the same pair of autosomes can be independently co-opted for the function of sex chromosomes (e.g. [71,75,128]; for overview in amniotes see [34]), or there might be turnovers of sex determination systems by the emergence of a new sex-determining locus within the same sex chromosome pair [66,129] (cases 15, 18 and 20 in figure 2).…”
Section: Is the Sex Chromosome Differentiationmentioning
confidence: 99%
“…Even highly differentiated, cytogenetically detectable sex chromosomes can be replaced by poorly differentiated ones, as supported by results in basilisks and Paroedura geckos [130][131][132] (case 10 in figure 2). Ogata et al [66] revealed that the heteromorphic sex chromosome systems probably returned to homomorphy through hybridization in the Japanese wrinkled frog Glandirana rugosa. In some cases, a simple system of two sex chromosomes changed into derived systems of three homologous sex chromosomes present in a population, e.g.…”
Section: Is the Sex Chromosome Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The sex-associated region on chromosome 4 could be a precursor to homomorphic sex chromosomes as we found no evidence of heteromorphic sex chromosomes. The potential sexdetermining region on chromosome 4 is small as there were only 2 sex-associated variants out of 418; therefore, a small and young homomorphic sex chromosome system could be present (Ogata et al 2021). Studies on sex chromosome evolution have shown that sex chromosomes usually evolve from homomorphic to heteromorphic (Charlesworth et al 2005).…”
Section: Evidence Of a Sex-associated Region In Bluehead Suckersmentioning
confidence: 99%
“…The Japanese soil‐frog Glandirana rugosa (formerly Rana rugosa ) is particularly well suited to address the above questions as it is highly diversified in sex‐determination and sex chromosomes. Previous studies on this species allow us to divide it into six geographic groups, based on sex‐determination, sex chromosomes, and mitochondrial DNA (Figure 1) (Miura, 2017; Ogata et al, 2021). The three populations, named ZW (northwestern Japan), XY (eastern Central Japan), and Neo‐ZW (western Central Japan), all have a heteromorphic sex chromosome system of ZW or XY on chromosome 7 in 13 haploid complements.…”
Section: Introductionmentioning
confidence: 99%